γ-ray detection from occasional flares in T Tauri stars of NGC 2071. I: observational connection - Filócomo, Agostina (2023)
NGC 2071 is a star-forming region that overlaps with three γ-ray sources detected by the Fermi Space Telescope. We propose that strong flare activity in T Tauri stars could produce γ-ray emission in a way that makes them a counterpart to some unidentified sources detected by the Large Area Telescope aboard the Fermi satellite. We have performed a spectral and temporal analysis for two Fermi data sets: the first 2 yr and the entire 14 yr of observations. We have found that the γ-ray source is detectable at 3.2σ above the background at energies above 100 GeV during the first 2 yr of observation. The analysis of the expected frequency of the highest energy flares occurring in T Tauri stars is consistent with our estimate. In addition, we have determined the minimum energy of the flare that would produce γ-ray emission, which is ~5 × 1037 erg. This agreement becomes a hard observational constraint supporting previous hypotheses about rare flares as the origin of unidentified γ-ray sources in star-forming regions.